2011
DOI: 10.1523/jneurosci.4016-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Integrative Proteome Analysis of Peripheral Nerve Myelin Identifies Novel Myelin Proteins and Candidate Neuropathy Loci

Abstract: Peripheral nerve myelin facilitates rapid impulse conduction and normal motor and sensory functions. Many aspects of myelin biogenesis, glia-axonal interactions, and nerve homeostasis are poorly understood at the molecular level. We therefore hypothesized that only a fraction of all relevant myelin proteins has been identified so far. Combining gel-based and gel-free proteomic approaches, we identified 545 proteins in purified mouse sciatic nerve myelin, including 36 previously known myelin constituents. By ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
195
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(199 citation statements)
references
References 106 publications
(152 reference statements)
2
195
0
2
Order By: Relevance
“…Therefore, the exon 1B isoform is expressed in vivo at least at the same level as, or even higher than, the exon 1A transcript ( Figure 2C). However, while Mtmr2 is developmentally regulated (12), this does not appear to be due to an increase in either transcript, which makes Mtmr2 similar to Pmp22 (29).…”
Section: The Mtmr2-2 Mrna Is Expressed In Schwann Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the exon 1B isoform is expressed in vivo at least at the same level as, or even higher than, the exon 1A transcript ( Figure 2C). However, while Mtmr2 is developmentally regulated (12), this does not appear to be due to an increase in either transcript, which makes Mtmr2 similar to Pmp22 (29).…”
Section: The Mtmr2-2 Mrna Is Expressed In Schwann Cellsmentioning
confidence: 99%
“…In mice, conditional loss of Mtmr2 in Schwann cells causes neuropathy with myelin outfoldings reminiscent of CMT4B1, whereas the loss of the gene in motor neurons does not cause axonal or myelination phenotypes (11). Furthermore, Mtmr2 expression is developmentally regulated during peripheral myelination (12), and knock-down of Mtmr2 in cultured Schwann cells decreases proliferation and increases cell death (13). However, there is evidence that Mtmr2 is important for neurons in vivo, based on genetic interactions between Mtmr2 and Fig4 in mouse models of CMT4B1 and CMT4J, respectively (14).…”
Section: Introductionmentioning
confidence: 99%
“…They are required for proper maintenance of the peripheral myelin sheath and Schwann cell compartmentalisation with their integral role reflected in the observation that they account for 16% of PNS myelin protein by weight. 13 In PRX-null mice the nerve fibres appear grossly normal but there is disruption of the cytoplasmic bands (Cajal bands) and impaired Schwann cell elongation during nerve growth which leads to a reduction in nerve conduction velocity and causes focal hypermyelination and demyelination which are hallmarks of the CMT4F phenotype. 14 A number of PRX variants have been described in the literature, 6,7,9 including the variant we identified (R1070*).…”
Section: Discussionmentioning
confidence: 99%
“…This unique biochemical composition has permitted both PNS and CNS myelin to be purified by biochemical fractionation procedures, which in turn has allowed this membrane specialization to be thoroughly characterized using mass spectrometry (56,57). These studies revealed a previously unappreciated complexity to myelin and permitted follow-up studies on novel myelin proteins.…”
Section: Proteomic Approaches To Studying Glial Cell Functionmentioning
confidence: 99%
“…For example, comparison of PNS and CNS myelin proteomes, together with unbiased immunostaining, revealed that N-ethylmaleimide-sensitive factor is highly enriched in Schwann cells surrounding nodes of Ranvier (56). Similarly, Septin 9, which is mutated in hereditary neuralgic amyotrophy, was identified as a PNS myelin protein that is dramatically increased in a mouse model of demyelinating neuropathy (57). Because of the ease of myelin purification, investigators have begun to analyze differences in myelin composition from models of nervous system diseases (e.g.…”
Section: Proteomic Approaches To Studying Glial Cell Functionmentioning
confidence: 99%